Gold Plate Electrodes Functionalized by Multiwall Carbon Nanotube Film for Potentiometric Thallium(I) Detection - Hassan, Saad S. M. (Nanomaterials (Basel), 2019)
Solid-contact potentiometric ion-selective electrodes (SC-ISEs) for thallium determination have been designed using multiwall carbon nanotubes (MWCNTs) as the ion-to-electron transducer. Dispersed MWCNTs were drop-casted over a gold plate electrode. Two different crown ethers were used in the sensing membrane for the recognition of thallium (I). Sensorsbased on dibenzo-18-crown-6 (DB18C6) as a neutral carrier and NaTPB as an anionic additive exhibited a near Nernstian response of 57.3 mV/decade towards Tl(+) ions over the activity range 4.5 × 10(−6)–7.0 × 10(−4) M, with a limit of detection of 3.2 × 10(−7) M. The time required to achieve 95% of the steadyequilibrium potential was <10 s. The complex formation constant (log β(ML)) between dibenzo-18-crown-6 and thallium (I) (i.e., 5.99) was measured using the sandwich membrane technique. The potential response was pH independent over the range 3.0–9.5. The introduction of MWCNTs as an electron-ion-transducer layer between gold plate and the sensing membrane lead to a smaller membrane resistance and a large double layer capacitance, which was proven using impedance spectra and chronopotentiometry (i.e., 114.9 ± 12 kΩ, 52.1 ± 3.3 pF, 200 ± 13.2 kΩ, and 50 ± 4.2 µF). Additionally, reduction ofthe water layer between the sensing membrane and the underlying conductor wastested. Thus, it is clear that MWCNTs can be used as a transducing layer in SC-ISEs. The proposed sensor was introduced as an indicator electrode for potentiometric titration of single and ternary mixtures of I(−), Br(−), and S(2−) anions.